Análise da expressão da proteína de reparo Kin 17 em células em cultura Bm5 e em tecidos larvais de Bombyx mori L - Rando, Fabiana dos Santos (2013)
Bombyx mori (Linnaeus, 1758) popularly known as silkworm silk, is an insect of great economic importance in the silk production and it is also the second organism used as a model organism for molecular studies. Environmental stress that causes viral or bacterial infection is one of the key factors in production decay. The repair kin17 protein is a major protein associated with cellular stress, DNA replication and RNA processing. In this study, our aim was to detect kin17 at 5th instar larval tissues from B. mori, including silk gland, fat body, ovaries, testicles, Malpighian tubules and nervous system. Protein extracts were also analyzed for cell culture of B. mori, lineage of Bm5, infected at different periods (0, 12, 24 and 48 hours) with the baculovirus BmNPV. Samples were extracted for each tissue and then analyzed through western blotting protocol using monoclonal antibodies against human kin17.The results showed an expected ~47kDa band on all tissues, except for the silk gland samples. The band was remarkably strong for the fat body and testicle samples. Surprisingly, an additional ~40kDa band was detected, being more expressive in the Malpighian tubules, nervous system and fat body. In samples extracted from infected and control cell culture showed, also, two fractions with the same molecular weight observed in larval tissues. Perhaps, the lower mass protein might represent an unknown isoform of kin17 in B. mori. In conclusion, the detection of the two kin17 isoforms offers new perspectives in the understanding of the cellular role of this protein.